n-HEXANE NEUROPATHY DUE TO SHOEMAKING: REPORT OF FIVE CASES - K. Sadeghniat; G. Pooryaghoob; E. Rafeemanesh (Acta Medica Iranica, 2005)
n-hexane neuropathy has been described after glue sniffing and industrial exposure. Onset may be subacute and reminiscent of Guillain-Barre' syndrome. Five patients (15-18 years old) presented with paresthesia, severe weakness of the extremities particularly lower extremities, as well as muscular atrophy, total areflexia and gait disturbances were admitted in hospital in March 2003. All of these boys were workers of a small footwear production unit. They worked as gluers of leather pieces. Nerve conduction velocity studies showed latency prolongation and cerebrospinal fluid (CSF) analysis showed normal protein. In the workplace assessment, it was found that hexacarbone-containing adhesives were used in an inappropriate ventilated place and without any personal protective devices. These patients were re-examined 8 months later. Sensory and autonomic symptoms were alleviated but two of them still had gait disturbance and decreased reflexes.